Building Organizational Citizenship Behavior Through Psychological Contract Mediation and Exogenous Variables Transformational Leadership and Organizational Support of Ny. Suharti Fried Chicken Restaurant Employees - Syahril, Imran; Subiyanto, Didik; Kurniawan, Ignatius Soni (Jurnal Manajemen Bisnis, 2022)
Research aims: This study aims to find out the effect of the strategy on building organizational citizenship behavior because the low level of organizational citizenship behavior causes the company to be unable to increase its effectiveness.Design/Methodology/Approach: In this study, the total population was 70 employees of fried chicken Ny. Suharti. The data collection method used the questionnaire method, while the technique for data analysis employed the classic assumption test, hypothesis testing, linear regression, and Sobel Test.Research findings: From this study, we found that (1) there was a positive result and significant effect of transformational leadership on psychological contracts (Y1), (2) there was a positive result but not significant effect of organizational support on psychological contracts, (3) there was a positive result with significant effect of transformational leadership on organizational citizenship behavior, (4) there was a positive result with significant effect of organizational support on organizational citizenship behavior, (5) there was a positive result but not significant effect on the influence of organizational support on psychological contracts, (6) there was a positive result but not significant effect of transformational leadership on organizational citizenship behavior, and (7) there was a positive result but not significant effect of the organizational support on organizational citizenship behavior, with the psychological contract variable as a mediating variable on employees of fried chicken restaurant Ny. Suharti.Theoretical contribution/Originality: This study contributes to the understanding of the effect of transformational leadership on psychological contracts, organizational support on psychological contracts, transformational leadership on organizational citizenship behavior, organizational support on organizational citizenship behavior, organizational support on psychological contracts, and organizational support on organizational citizenship behavior, with the psychological contract variable as a mediating variable on employees.Practitioner/Policy implication: Based on the analysis results, not all variables had a positive and significant effect except for transformational leadership on psychological contracts, transformational leadership on organizational citizenship behavior, and organizational support on organizational citizenship behavior; other than these variables, it showed positive reluts but insignificant.Research limitation/Implication: The research was only conducted at the fried chicken restaurant, Ny. Suharti. Therefore, the data collected had a low level of normality.